Convergence of the Generalized Steffensen Method in Riemannian Manifolds - Prasad, Chandresh; Kumar Parida, Pradip (Sarajevo Journal of Mathematics, 2025)
In this article, we present semilocal convergence of the generalized Steffensen method in Riemannian manifolds to find the singular points of a vector field. We establish the convergence under the Kantarovich–Ostrowski’s conditions. Finally, two examples are given to show the applicability of our convergence analysis.